PENGARUH CITRA MEREK, INOVASI PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN SAUS SAMBAL SASA DI KOTA BATAM - H, Valencia (LPPM Universitas Putera Batam, 2025)
This study aims to determine the influence of brand image variables, product innovation and advertisingon purchasing decisions for Sasa Sambal Sauce in Batam City. The sampling technique uses theLemeshow formula because the number of samples is unknown, so the number of respondents in thisstudy is 100 respondents. The data is processed using SPSS (Statistical Product and Service Solution)version 25. The analysis method used is descriptive statistical test, validity test, reliability test, classicalassumption test, influence test, hypothesis test. The results of the study indicate that brand image,product innovation and advertising have a significant effect simultaneously on purchasing decisions forSasa Sambal Sauce in Batam City. The results of the determination coefficient analysis state that brandimage, product innovation and advertising have a significant effect on purchasing decisions for SasaSambal Sauce by 24.9%. While the rest is influenced by other variables not studied.